Effect of Mix Parameters on the Strength Performance of Waste Plastics Incorporated Concrete Mixes. (4th December 2014) - Malkapur, Santhosh M.; Anand, Ashish; Pandey, Amit Prakash; Ojha, Alok; Mani, Nimesh; Mattur, Narasimhan Chandrashekara
Abstract : Disposal of solid wastes has been a major problem all over the world. Out of all the different types of solid wastes, the major challenge of disposal is posed by the ever increasing volumes of plastic wastes. While several methods are in practice, producing newer useful materials by recycling of such plastic wastes is, by far, the best method of their disposal. One such possible method is to use the waste plastics as an ingredient in the production of the concrete mixes in the construction industry. The present study aims to investigate the relative contributions of the various mix parameters to the mechanical properties of concrete mixes produced with waste plastics as partial replacement (10–30% by volume) to coarse aggregates. Initially, strength test results of a set of trial mixes, selected based on Taguchi's design of experiments (DOE) method are obtained. A detailed analysis of the experimental results is carried out to study the effect of using waste plastics as a partial replacement to coarse aggregates on the strength parameters of these concrete mixes. It is found that all these trial mixes have performed satisfactorily in terms of workability in the fresh state and strength properties in their hardened state.